1998
DOI: 10.1097/00003643-199801000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal morphine and continuous femoral 3-in-1 block for pain after major knee surgery under spinal anaesthesia

Abstract: Three patients in the morphine group and one patient in the femoral group did not need any additional Major knee surgery is associated with moderate or oxycodone. In the morphine group on average 2.8 severe post-operative pain. Intrathecal morphine and (range 0-7) and in the femoral group 3.2 (0-5) adcontinuous femoral 3-in-1 block were compared proditional doses of oxycodone were needed during the spectively in 40 patients for pain after major knee 24 h observation period. The mean pain scores were surgery un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…In previous studies, intrathecal morphine has been considered more effective, except for pruritus, in comparison with femoral nerve block [9, 10]. A low dose of intrathecal morphine was considered safer than the femoral nerve blockade [11].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, intrathecal morphine has been considered more effective, except for pruritus, in comparison with femoral nerve block [9, 10]. A low dose of intrathecal morphine was considered safer than the femoral nerve blockade [11].…”
Section: Discussionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6)(7) Importance of the current investigation was the comparison of three different administration routes in the same study design. In this study, we found that 100 μg morphine intrathecal, 10 mg intraarticular and 10 mg intramuscular injections revealed an effective postoperative analgesia after arthroscopic knee surgery compared to the control group receiving no morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews which have evaluated the literature data on IA administration of opioids revealed that the quality of most of the studies involving IA administration of morphine were weak. (1,6,(15)(16)(17) Intraarticular use of morhine is contraversial with some positive (1,(16)(17)(18) and some negative results. (19)(20)(21) Thus the authors recommended further randomized controlled trials to clarify the contradictory results published in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations